Impact of malnutrition on immunity and infection - França,TGD (2009)
Malnutrition may be a consequence of energy deficit or micronutrient deficiency. It is considered the most relevant risk factor for illness and death, particularly in developing countries. In this review we described the magnitude of this problem, as well as its direct effect on the immune system and how it results in higher susceptibility to infections. A special emphasis was given to experimental models used to investigate the relationship between undernutrition and immunity. Malnutrition is obviously a challenge that must be addressed to health authorities and the scientific community.